2016
DOI: 10.3389/fpls.2016.01375
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Petal Abscission Zone and Functional Analysis of an Aux/IAA Family Gene RhIAA16 Involved in Petal Shedding in Rose

Abstract: Roses are one of the most important cut flowers among ornamental plants. Rose flower longevity is largely dependent on the timing of petal shedding occurrence. To understand the molecular mechanism underlying petal abscission in rose, we performed transcriptome profiling of the petal abscission zone during petal shedding using Illumina technology. We identified a total of 2592 differentially transcribed genes (DTGs) during rose petal shedding. Gene ontology term enrichment and pathway analysis revealed that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 69 publications
4
58
0
Order By: Relevance
“…The expression of RhERF1 was significantly reduced by ethylene treatment, while the expression of RhERF4 was significantly induced by auxin (Figure a,b). We then examined the expression of RhERF1 and RhERF4 in the petal AZ during six sequential stages of flower opening as described previously (Gao et al ., ). Quantitative real‐time (qRT)‐PCR analysis showed that RhERF1 transcript levels decreased (Figure c), while RhERF4 expression was the highest in stage 2 and then decreased (Figure d).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The expression of RhERF1 was significantly reduced by ethylene treatment, while the expression of RhERF4 was significantly induced by auxin (Figure a,b). We then examined the expression of RhERF1 and RhERF4 in the petal AZ during six sequential stages of flower opening as described previously (Gao et al ., ). Quantitative real‐time (qRT)‐PCR analysis showed that RhERF1 transcript levels decreased (Figure c), while RhERF4 expression was the highest in stage 2 and then decreased (Figure d).…”
Section: Resultsmentioning
confidence: 97%
“…For expression pattern analysis, flower opening stages were defined as previously described (Gao et al ., ). Briefly these are: stage 1, bud with completely opened sepal; stage 2, bud with outermost petal layer loosened; stage 3, flower with outermost petal layer opened; stage 4, flower with inner petal layer loosened; stage 5, fully opened flower with visible anthers; stage 6, fully opened flower with abscised petals.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…After vacuum agroinoculation, the plantlets are transferred to soil. TRV‐infected plantlets flower about 2 months post‐inoculation, upon which time the efficiency can be evaluated by observing flower characteristics, such as flower development (Chen et al ), abscission (Gao et al ), and petal expansion (Ma et al ; Luo et al ).…”
Section: Introductionmentioning
confidence: 99%